A review on the technology transfer models, knowledge-based and organizational learning models on technology transfer - Raduan Che Rose; Sazali Abdul Wahab; Jegak Uli; Haslinda Abdullah (2009)
The main objective of this paper is to contribute to the existing Technology Transfer (TT) literature by reviewing the evolution and development of the previous TT models which include the traditional TT model, models developed after 1990s, other related theoretical foundations underlying TT models, and the current TT models which have strong influence of knowledge-based view (KBV) and organizational learning (OL) perspectives. Since the current management researchers have a strong focus on TT within strategic alliance and other collaborative ventures, this review highlights the significant influence of KBV and OL perspectives on inter-firm TT models. This review attempts to help stimulate the direction of both future theoretical and empirical studies on inter-firm technology transfer specifically 1) on how KBV and OL perspectives could play significant role in explaining the complex relationships between the supplier and recipient in inter-firm technology transfer 2) the tradeoffs that involve between properties of technology, protecting proprietary technologies, competitiveness of the supplier, willingness to transfer technology, and learning attitudes of the recipient in strategic alliances and JVs, and 3) on how KVB and OL perspectives could be integrated in a holistic model to explain the relationships between knowledge transferred, the recipient, the supplier, relationship characteristics and degree of technology transfer.